2014
DOI: 10.1590/s1679-78252014000900004
|View full text |Cite
|
Sign up to set email alerts
|

A study on the nonlinear stability of orthotropic single-layered graphene sheet based on nonlocal elasticity theory

Abstract: Recently, graphene sheets have shown significant potential for environmental engineering applications such as wastewater treatment. In the present work, the posbuckling response of orthotropic single-layered graphene sheet (SLGS) is investigated in a closedform analytical manner using the nonlocal theory of Eringen. Two opposite edges of the plate are subjected to normal stresses. The nonlocality and geometric nonlinearity are taken into consideration, which arises from the nanosized effects and mid-plane stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…(III) For a magneto-electro-elastic nanoplate, the buckling load and vibration frequency decrease linearly with electric potential, spring and shear coefficients of the Pasternak foundation, and increases with magnetic potential. Asemi et al [9] presented nonlocal theory to study the free vibration of orthotropic SLGS resting on a Pasternak foundation under shear in-plane load based on classical plate theory (CLPT) and used the combined Galerkindifferential quadrature method to solve the obtained equation. They concluded that increasing nonlocal parameter reduces the non-dimensional frequency of the SLGS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(III) For a magneto-electro-elastic nanoplate, the buckling load and vibration frequency decrease linearly with electric potential, spring and shear coefficients of the Pasternak foundation, and increases with magnetic potential. Asemi et al [9] presented nonlocal theory to study the free vibration of orthotropic SLGS resting on a Pasternak foundation under shear in-plane load based on classical plate theory (CLPT) and used the combined Galerkindifferential quadrature method to solve the obtained equation. They concluded that increasing nonlocal parameter reduces the non-dimensional frequency of the SLGS.…”
Section: Introductionmentioning
confidence: 99%
“…Asemi et al. [9] presented nonlocal theory to study the free vibration of orthotropic SLGS resting on a Pasternak foundation under shear in-plane load based on classical plate theory (CLPT) and used the combined Galerkin-differential quadrature method to solve the obtained equation. They concluded that increasing nonlocal parameter reduces the non-dimensional frequency of the SLGS.…”
Section: Introductionmentioning
confidence: 99%
“…The vibrations of tensioned nanobeams using the nonlocal beam theory are investigated by Bagdatli (2015). The nonlinear frequencies for fixed-fixed and simply-simply supported Euler-Bernoulli nanobeams are presented.…”
Section: Introductionmentioning
confidence: 99%
“…Asemi et al [30] presented an axisymmetric buckling analysis of circular SLGS using Eringen's theory. Additionally, Asemi et al [31] used nonlocal theory of Eringen to simulate postbuckling response of orthotropic SLGS.…”
Section: Introductionmentioning
confidence: 99%